COASTAL VULNERABILITY ANALYSIS IN PADANG PARIAMAN REGENCY, WEST SUMATERA - Ramadhan, Fauzi; Mubarak, Mubarak; Elizal, Elizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
This research was conducted in June to July 2019. It aimed to analyzed the vulnerability and the shoreline change of coastal area of Padang Pariaman Regency, West Sumatera Province. Survey method with direct field observations were applied and different satellite imageries were also used to find out the shoreline change of coast under study. The results showed that there five categories of changes, namely high and low accretion (>2.1 m yr-1; 1 - 2 m yr-1); stable condition (-1 to 1 m yr-1); and high and low erosion (<-2 m yr-1; -1 to -2 m yr-1). Furthermore, the percentages of coastal vulnerability of the areas under study can be classified into five categories such as Very Low Condition (17.27 %), Low Condition (39.68 %), Medium Condition (29.02 %), High Condition (8.88 %), and Very High Condition (5,75 %). In addition, the districts of Sungai Limau and Batang Gasan had very high vulnerability condition.